Congenital Anomaly in 100 Pregnant Women in a District Hospital of Bangladesh - Barua, Hena Rani; Barua, Rita Rani; Dhar, Swapna Rani; Barua, Sushanta; Barua, Ajoy Kishore; Prasad, Indrajit; Ansari, M Abdul Jalil; Begum, Kohinoor (Journal of Dhaka Medical College, 2017)
Background: Congenital anomalies are a major cause of stillbirths and neonatal mortality. The pattern and prevalence of congenital anomalies may vary over time or with geographical location. Objective: To determine the types of congenital fetal abnormality and to find out the outcome of fetus. Material and methods: One hundred cases of pregnant women with singleton pregnancy having congenital fetal anomaly were studied. The study was performed at the in-patient department of Obstetrics and Gynecology in Rangamati Medical College Hospital, Rangamati, Bangladesh from January 2016-December 2016. The newborn were examined for the presence of congenital anomalies and mothers were interviewed for socio-demographic variables. Results: During the study period, it was observed that most of the women (63%) belonged to age group between 21 and 30 years. More common congenital abnormalities were anencephaly (21%), bilateral hydronephrosis (17%), hydrocephalous (11%) and ventriculomegaly (8%). The deliveries were mostly (89%) normal vaginal and the rest were caesarean section. Male fetuses are more prone to develop congenital abnormality. Congenital anomalies were more likely to be associated with still born, IUD, prematurity, multiparity, consanguinity and perinatal death. Conclusion: Public awareness about preventable risk factors is to be created and early prenatal diagnosis and management of common anomalies is strongly recommended. J Dhaka Medical College, Vol. 25, No.2, October, 2016, Page 105-109